Peripheral cemento-ossifying fibroma: Report of a case in an elderly patient - Shruti Sinha; Siva Prasad Reddy Enja; Sunira Chandra; Suzanne Nethan (Wolters Kluwer Medknow Publications, 2014)
The peripheral cemento-ossifying fibroma (PCOF) is an osteogenic neoplasm and is believed to arise from the periodontal ligament. It accounts for 3.1% of all oral tumors and 9.6% of all gingival lesions. It frequently occurs in the maxillary anterior region in teenagers and young adults, and has a female predilection. Trauma, local irritation due to calculus, ill-fitting dentures and faulty restorations, and hormonal disturbances are the known predisposing factors. An early diagnosis and surgical excision is required to prevent its recurrence. Here we present a case of PCOF with a history of just two months, occurring in an elderly female involving the edentulous mandibular posterior region.